Doctors in India A Statistical Study - Planning Commission (Planning Commission Government of India, 1968)
The 1959 Statistical Study on Doctors in India, conducted by the Planning Commission, provides a comprehensive analysis of the country’s medical workforce, covering composition, qualifications, age, gender, and regional disparities. The study estimated 71,600 doctors in 1956, including specialists, graduates, and licentiates, with women comprising only 7.5%. Significant urban-rural and regional imbalances were identified, with rural areas severely underserved. Salary disparities and concentration of doctors in government employment were noted. The report emphasizes the need for improved medical registration, standardized data collection, and accurate tracking of active doctors. These insights are crucial for healthcare planning, particularly for addressing shortages and ensuring equitable access to medical services across India.
Planning Commission Perspective Planning Division
Planning Commission Perspective Planning Division
Keywords: Doctors; India; 1959; Medical Workforce; Rural Healthcare; Doctor-Patient Ratio; Specialist Doctors; Graduate Doctors; Licentiates; Regional Disparities; Medical Registers; Healthcare Planning